Enhancing Students’ Writing Procedure Text Using the Scramble Method - Arief Pamuji Arief (Program Pendidikan Bahasa Inggris Universitas Tridinanti, 2023)
Students can communicate their ideas more effectively by writing down their ideas. Nevertheless, writing still presents challenges for students. Therefore, this research aims to determine the impact of the scramble method in improving students' procedural text writing skills and to find out what aspects of writing improve after using the scramble method. The experimental method using a pre-experimental design was used to conduct this research. Since the total population of this study was 26 students nursing students in the fourth semester, all the students were taken as samples using the study population sampling technique. To measure the students’ writing ability, pre-and post-tests of procedures writing were applied. To analyze the data, a t-test of paired sample t-test was used. The result revealed that the scramble method was effective in improving students’ writing skills. The findings revealed that the t-obtained (14.08) was higher than the t-table (2.059) at a significant p-value level less than 0.5. It indicated that the scramble method improved students' writing skills. Besides, students' writing skills increased in the following areas: vocabulary (1.85), organization (1.58), structure (1.15), content (0.81), and mechanism (0.65). Students' writing improved with the scramble method as they actively participated in reassembling scrambled sentences, encouraging their enthusiasm to write on engaging subjects.